Local trends of antibiotic prescription for necrotizing fasciitis patients in two tertiary care hospitals in central Malaysia - Rampal, Sanjiv; Ganesan, Thanusha; Sisubalasingam, Narresh; Neela, Vasantha Kumari; Tokgöz, Mehmet Ali; Arunasalam, Arun; Ab Halim, Mohd Asyraf Hafizuddin; Shamsudin, Zulfahrizzat; Kumar, Suresh; Sinniah, Ajantha (MDPI AG, 2021)
Background: Necrotizing fasciitis (NF) is a rapidly progressive inflammatory infection of the soft tissue (also known as the fascia) with a secondary necrosis of the subcutaneous tissues, leading to a systemic inflammatory response syndrome (SIRS), shock and eventually death despite the availability of current medical interventions. The clinical management of this condition is associated with a significant amount of morbidity with a high rate of mortality. The prognosis of the disease is affected by multiple factors, which include the virulence of the causative pathogen, local host immunity, local wound factors and empirical antibiotics used. The local trends in the prescription of empirical antibiotics are often based on clinical practice guidelines (CPG), the distribution of the causative microorganism and the cost-effectiveness of the drug. However, there appears to be a paucity of literature on the empirical antibiotic of choice when dealing with necrotizing fasciitis in the clinical setting. This paper will outline common causative microorganisms and current trends of prescription in two tertiary centres in Central Malaysia. Methods: This was a cross-sectional study using retrospective data of patients treated for NF collected from two tertiary care hospitals (Hospital Seremban and Hospital Ampang) in Central Malaysia. A total of 420 NF patients were identified from the five years of retrospective data obtained from the two hospitals. Results: The top three empirical antibiotics prescribed are ampicillin + sulbactam (n = 258; 61.4%), clindamycin (n = 55; 13.1%) and ceftazidime (n = 41; 9.8%). The selection of the antibiotic significantly impacts the outcome of NF. The top three causative pathogens for NF are Streptococcus spp. (n = 79; 18.8%), Pseudomonas aeruginosa (n = 61; 14.5%) and Staphylococcus spp. (n = 49; 11.7%). The patients who received antibiotics had 0.779 times lower chances of being amputated. Patients with a lower laboratory risk indicator for necrotizing fasciitis (LRINEC) score had 0.934 times lower chances of being amputated. Conclusions: In this study, the most common empirical antibiotic prescribed was ampicillin + sulbactam followed by clindamycin and ceftazidime. The antibiotics prescribed lower the risk of having an amputation and, hence, a better prognosis of the disease. Broad-spectrum empirical antibiotics following surgical debridement reduce the mortality rate of NF.